The Effect of Transformational Leadership Style and Communication on Employee Job Satisfaction at the Regional Personnel Agency (BKD) of Bima District - Sri Rahayu; Mawar Hidayanti (GoodWill, 2026)
This study examined the effect of transformational leadership style and communication on employee job satisfaction at the Regional Personnel Agency (BKD) of Bima District, Indonesia. Employee job satisfaction is considered an important factor influencing organizational performance, commitment, and public service quality in government institutions. However, preliminary observations indicated several problems related to leadership practices, ineffective communication, and limited employee support within the organization. Therefore, this research aimed to analyze both the partial and simultaneous effects of transformational leadership and communication on employee job satisfaction. The study employed a quantitative associative research design. Data were collected through structured questionnaires distributed to 39 civil servant employees selected using purposive sampling techniques. The instruments were measured using a five-point Likert scale and analyzed using multiple linear regression with the assistance of SPSS software. The results revealed that transformational leadership had a positive and significant effect on employee job satisfaction (t = 3.861; p < 0.05). Communication also showed a positive and significant effect on employee job satisfaction (t = 5.372; p < 0.05). Simultaneously, transformational leadership and communication significantly influenced employee job satisfaction (F = 32.860; p < 0.05), with a coefficient of determination of 64.6%. These findings indicate that effective leadership and communication practices play a crucial role in improving employee satisfaction and organizational effectiveness in public sector institutions.